Estudo computacional dos efeitos farmacológicos das miotoxinas Lys49 de serpentes (Familia:Viperidae): modelos moleculares para citotoxidade e miotoxidade - Gomes, Antoniel Augusto Severo (2014)
Snakebites are and global endemic problem and the study of its components is important to understand and prevent them. Among its components, phospholipase A2 have been strongly studies as Lys49 myotoxins. However, understanding the molecular mechanisms of its pharmacological effects remains controversial until now. This work studied the Lys49 myotoxins pharmacological structural determinants, emphasizing cytotoxic and myotoxic effects. Protein sequence analysis as well as molecular docking with myotoxin Bn IV and VEGFR-II receptor and different anionic molecules, such as phosphate, heparin and lipopolysaccharide were performed. Sequence analyses showed defied regions within Lys49 myotoxins group, especially cationic regions. In accordance with this, molecular dockings performed in this work observed the presence of anionic non-specific sites, also a heparin recognition site. Molecular dockings between myotoxin Bn IV and VEGFR-II were satisfactory and indicated C-terminal tail as an important interactive region. Our results determine cationic regions as important for cytotoxic effects and bring a new molecular approach to the myotoxic effects, via VEGFR-II. In additional, molecular cytotoxic and myotoxic models for myotoxic Lys49 were presented